2013
DOI: 10.1145/2400682.2400691
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fundamental design choices in single-ISA heterogeneous multicore architectures

Abstract: Single-ISA heterogeneous multicore processors have gained substantial interest over the past few years because of their power efficiency, as they offer the potential for high overall chip throughput within a given power budget. Prior work in heterogeneous architectures has mainly focused on how heterogeneity can improve overall system throughput. To what extent heterogeneity affects per-program performance has remained largely unanswered. In this article, we aim at understanding how heterogeneity affects both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
0
15
0
11
Order By: Relevance
“…These proposed techniques focus on improving the overall chip-level throughput. The work in [21] explores the per-program performance in addition to the overall chip level throughput when using heterogeneous multi-core processors.…”
Section: Related Workmentioning
confidence: 99%
“…These proposed techniques focus on improving the overall chip-level throughput. The work in [21] explores the per-program performance in addition to the overall chip level throughput when using heterogeneous multi-core processors.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, since the application requirement changes along the execution phases, it is necessary for dynamic application mapping and migration. Recently, substantial research efforts are made to accurately model the application performance under different cores [9] and conduct application mapping/scheduling and migration [10,11,12]. An analytical performance model is used and the fundamental design tradeoffs of single-ISA heterogeneous multi-core is studied [9].…”
Section: B-1mentioning
confidence: 99%
“…Such architectures include ARM's big.LITTLE [23] and Intel's QuickIA [6], which combines a Xeon server CPU with an energy efficient Atom CPU in a single system. Previous work on single-ISA heterogeneous architectures has shown that database systems need to be adapted in order to optimally use heterogeneous processors [3] and that job-to-core mapping in such a setting is important and challenging [29].…”
Section: Related Workmentioning
confidence: 99%
“…Although multi-core scaling helps to alleviate dark silicon, it is just a workaround as the fraction of transistors that can be powered continues to decrease with each process generation [2]. Future processors will thus need to become more heterogeneous, i.e., be composed of cores with asymmetric performance and power characteristics to use transistors effectively [2,7,8,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation